Lexical and functional substandard in forensic linguistics - Z. I. Mineeva (Шаги, 2025)
The article focuses on the analysis of lexemes of the standard language and sublanguage, including jargon and obscenities, in terms of their connection with the speech act of insult. The author takes primarily the position of a practitioner of linguistic expertise. The relevance of the topic is driven by the demand for the most accurate and exhaustive description of the criteria for attributing a particular word, phrase, sentence to the language units of a speech act of insult. The aim of the research is to define the conditions under which different types of substandard lexical units participate in a speech act of insult. Semantic, stylistic and pragmatic methods are used in the research, as well as cases from the author’s practice in the field of forensic linguistics. The results of the study distinguish two types of substandard: a) the lexical substandard, which includes units of jargon, vernacular and obscene vocabulary; b) the functional substandard, including the vocabulary of the literary language used in invective. The analysis made it possible to determine the conditions under which obscene pejorative vocabulary with the negative characteristic of a person participates in a speech act of insult. It is concluded that there are conditions under which the vocabulary of the literary language is also included in the speech act of insult. The factor of lexical units belonging to a lexical or functional substandard is the key criterion for an expert linguist when analyzing a controversial text.